2018
DOI: 10.22365/jpsych.2018.293.264
|View full text |Cite
|
Sign up to set email alerts
|

Is impulsivity in part a lithium deficiency state?

Abstract: L ithium mechanisms of action are related to the function of many enzymes, hormones, vitamins, and growth factors. In humans, lithium treatment has been associated with humoral and structural evidence of neuroprotection, such as increased expression of antiapoptotic genes, inhibition of cellular oxidative stress, synthesis of brain-derived neurotrophic factor, cortical thickening, increased grey matter density, and hippocampal enlargement. Lithium, in pharmacological doses, has been used successfully in treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In either way, the suicide victims might be lithium deficient. While lithium deficiency causes behavioral changes, such as diminished conditioned avoidance behavior in animals [ 9 , 34 ], that lithium deficiency was suggested to precipitate impulsivity in humans [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In either way, the suicide victims might be lithium deficient. While lithium deficiency causes behavioral changes, such as diminished conditioned avoidance behavior in animals [ 9 , 34 ], that lithium deficiency was suggested to precipitate impulsivity in humans [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This molecule, in fact, is characterized primarily by DRD3 partial agonism and serotonin 5-HT1A partial agonism, while aripiprazole is more selective for DRD2 than DRD3 [40]. There is also a potential drug-drug interaction between carbolithium and cariprazine: while impulsivity has traditionally been linked to the dysregulation of serotoninergic and dopaminergic systems, some authors have suggested that lithium may reduce impulsivity levels through its ability to regulate these neurotransmitter systems [41].…”
Section: Discussionmentioning
confidence: 99%